FAKTOR-FAKTOR PENENTU INTENSI BERWIRAUSAHA MAHASISWA - Renny Dwijayanti (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
The purpose of this study is to determine and analyze the dominant factor as a determinant of the entrepreneurship intent of the students of the Department of Economic Education of the State University of Surabaya.This research uses explanatory research method, the sample used is 166 students from the total population of 286 students with purposiverandom sampling technique. The results showed that locus of control, subjective norms, and entrepreneurial attitudes affect the intention of student entrepreneurship. From the three determining variables of the entrepreneurship intentions, there is one dominant variable as determinant of student entrepreneurship intention, it is locus of control. The locus of control of students related to entrepreneurship is a personal belief in the success gained from the business and learning process. The implication of this research is students need to strengthen the formation ofentrepreneurial mindset to be able to grow their self-confidence on their own potentials.